Sensor Technologies 2013
DOI: 10.1007/978-1-4302-6014-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Wellness, Fitness, and Lifestyle Sensing Applications

Abstract: Physical fitness is not only one of the most important keys to a healthy body; it is the basis of dynamicand creative intellectual activity. -John F. Kennedy, 35th President of the United StatesChapter 9 considered how sensors are playing an increasingly important role in health-related applications, such as chronic disease management. Medically, health is sometimes described as the absence of one or more of the "five Ds": death, disease, discomfort, disability, and dissatisfaction. Consequently, the focus is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The availability of Microelectromechanical Systems (MEMS) and their development for miniaturized sensors, combined with integrated processing and communication technologies, enabled the development of wearable sensing devices for human body monitoring [1,15]. To obtain information regarding specific human locomotion parameters, one or more sensing devices are worn directly on relevant body parts and connected to a central processing hub for data collection and processing, forming a so-called Body Sensor Network [69].…”
Section: Inertial-based Motion Capturementioning
confidence: 99%
“…The availability of Microelectromechanical Systems (MEMS) and their development for miniaturized sensors, combined with integrated processing and communication technologies, enabled the development of wearable sensing devices for human body monitoring [1,15]. To obtain information regarding specific human locomotion parameters, one or more sensing devices are worn directly on relevant body parts and connected to a central processing hub for data collection and processing, forming a so-called Body Sensor Network [69].…”
Section: Inertial-based Motion Capturementioning
confidence: 99%
“…While the human brain is a very sophisticated processing unit perfected through millions of years of evolution, attempts to tap the outward flow of information have only now begun to attract serious interest and success in the practice of clinical healthcare and wellness monitoring. [66], [67] Electronic skin solutions to this problem have recently attracted significant interest, with surface electromyography being one of the applications targeted. [64], [68], [69] Systems capable of temperature, electrophysiological and strain sensing, that incorporate lightemitting diodes and photo-detectors, are described.…”
Section: Printed Light Sources and Imaging Systemsmentioning
confidence: 99%
“…As an alternative, wearable devices that monitor activity, store medical data and transmit data to base stations are a currently active revolution in personalized healthcare. [67] Such devices must provide reliable contact with the body as wearables, and be durable enough to be reusable.…”
Section: Printed Light Sources and Imaging Systemsmentioning
confidence: 99%
“…Recent works have shown that tracking measurements such as step counts, spent calories and body weight are very effective in lifestyle changes by motivating a person to engage in physical exercise (McGrath and Scanaill 2013). Additionally, by tracking measurements over time, he/she gets insights regarding his/her progress and he/she is able to experience the direct relation between his efforts and the actual outcome.…”
Section: Introductionmentioning
confidence: 99%